2014
DOI: 10.1007/s00586-014-3551-0
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the risk for symptomatic adjacent segment degeneration after lumbar fusion: analysis from a cohort of patients undergoing revision surgery

Abstract: In patients re-operated upon for ASD, pelvic retroversion and hyperlordosis are the main mechanisms of compensation for the unbalanced spine. Patients with PT above 21° and SS below 39° are at higher risk for symptomatic ASD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 23 publications
0
25
0
Order By: Relevance
“…28 In addition, a PT of > 21° and an SS of < 39° were perceived as factors for elevated risk for symptomatic ASD. 5 However, with cases of short fixation, Masevnin et al 21 failed to find statistically significant dependency between ASD and sagittal imbalance. In our study, there were no significant differences in spinal sagittal alignment between patients with and those without ASD in both groups.…”
Section: Discussionmentioning
confidence: 98%
“…28 In addition, a PT of > 21° and an SS of < 39° were perceived as factors for elevated risk for symptomatic ASD. 5 However, with cases of short fixation, Masevnin et al 21 failed to find statistically significant dependency between ASD and sagittal imbalance. In our study, there were no significant differences in spinal sagittal alignment between patients with and those without ASD in both groups.…”
Section: Discussionmentioning
confidence: 98%
“…Some studies have suggested that abnormal sagittal spinopelvic parameters play a significant role in ASD after lumbar fusion. 5,13,14 Kumar et al reviewed 83 patients with degenerative disc disease and concluded that patients who had an abnormal C-7 plumb line position and/or SS had a significantly higher rate of ASD. 13 Di Martino et al reported that patients with PT > 20° and SS < 40° were at higher risk than others for clinically evident ASD.…”
Section: Discussionmentioning
confidence: 99%
“…7,14 Additionally, it has been suggested that spinopelvic sagittal alignment may contribute to ASD. 5,13,21 However, most of these studies of the relationships between spinopelvic sagittal alignment and ASD did not evaluate standing radiographs of the whole spine, and they included various numbers of fused segments and levels of fusion that affect spinopelvic sagittal alignment. Therefore, little is still known about the relationship between spinopelvic alignment and ASD.…”
mentioning
confidence: 99%
“…1 The clinical outcomes of revision surgery are poor, and the many complications, especially durotomy, are more common than in primary surgery. 2,3 Several studies have evaluated the short-term results of revision 1,4 and the postoperative complications 5,6 in LSS patients after primary fusion and primary decompression. However, to our knowledge, no single-center studies with a long follow-up period and detailed analysis of outcome and risk factors for revision surgery have been conducted.…”
Section: Introductionmentioning
confidence: 99%